Metal‐free Nucleophilic α‐Azidation of α‐Halohydroxamates with Azidotrimethylsilane. Issue 12 (5th October 2021) - Lee, Chang Yoon; Kim, Sung‐Gon
Abstract: A mild and metal‐free synthetic method for α‐azido carbonyl derivatives via the nucleophilic α‐azidation of α‐halohydroxamates have been established. The reactions of trimethylsilyl azide with various α‐mono‐ and disubstituted azaoxyallyl cations, generated in situ from α‐halohydroxamates, afforded a wide range of hindered mono‐ and dialkyl α‐azido carbonyl derivatives in good yields in the presence of tetrabutylammonium fluoride as a catalyst. Abstract : Sterically hindered α‐azido carbonyls : Mild and efficient synthetic method of α‐azido carbonyl derivatives has been established using the nucleophilic α‐azidation of α‐halohydroxamates. The reaction of TMSN3 with various α‐mono‐ and disubstituted α‐halohydroxamates using TBAF as a catalyst produced a wide range of hindered α‐azido carbonyl derivatives in good yields.